Level of knowledge of mothers about the degree of dehydration in children with diarrhea: Pediatric Hospital Dr. Agustin Zubillaga (Boletin Médico de Postgrado, 2021)
A descriptive cross-sectional research was done to evaluate the level of knowledge of mothers about the degree of dehydration in children ≤ 5 years of age with diarrhea that were attended in the Pediatric Hospital Dr. Agustin Zubillaga during the period april-june 2018. The sample was made up of 60 mothers. A primary source and a questionnaire was used to collect data. Results show that 70% of mothers had regular knowledge about the degree of dehydration secondary to diarrhea in terms of definition, causes and complications of diarrhea. Regarding the knowledge of dehydration signs, 83.3% of mothers had deficient knowledge, 11.7% regular knowledge and 5% good level of knowledge. 46.7% of mothers had a deficient level of knowledge, 38.3% and 15% had regular and good level of knowledge about the measures necessary to prevent dehydration. In general, the level of knowledge that mothers of pediatric patients with diarrhea had is deficient in more than half of them (55%), while 38.3% had regular level and 6.7% good level. These results show the need to conduct information campaigns for mothers and their families about diarrhea and dehydration due to diarrhea by the authorities and medical personnel in general.
Keywords: diarrhea; mothers; child; dehydration; primary prevention